2001
DOI: 10.1037/0893-3200.15.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Maritally violent men's heart rate reactivity to marital interactions: A failure to replicate the Gottman et al. (1995) typology.

Abstract: In an attempt to replicate the J. M. Gottman et al. (1995) batterer typology, 58 men who had engaged in moderate-to-severe marital violence in the past year were studied. The sample was split into Gottman et al.'s Type 1 men (i.e., whose heart rates decreased, from baseline, during a marital conflict task) and Type 2 men (i.e., whose heart rates increased). The groups did not differ in the manner predicted on measures of marital violence, antisocial or aggressive-sadistic personality, drug dependence, criminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 33 publications
(113 reference statements)
3
72
0
Order By: Relevance
“…When psychopathy was used to examine the differentiate among batterer subtypes, psychopathic traits failed to differentiate among traditional batterer subtypes proposed by Gottman et al (1995) and Holtzworth-Munroe and Stuart (1994), among both non-convicted Holtzworth-Munroe et al, 2000, 2003Meehan et al, 2001) and convicted (Huss & Langhinrichsen-Rohling, 2006) samples. However, when other alternative batterer typologies were established, psychopathy proved to be useful to identify a specific batterer subtype characterized by displaying pathologically high anger levels (Eckhardt et al, 2008;Murphy et al, 2007), perpetrating premeditated (Stanford et al, 2008) and proactive IPV (Chase et al, 2001) and repeatedly reassaulting their partners (Gondolf & White, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When psychopathy was used to examine the differentiate among batterer subtypes, psychopathic traits failed to differentiate among traditional batterer subtypes proposed by Gottman et al (1995) and Holtzworth-Munroe and Stuart (1994), among both non-convicted Holtzworth-Munroe et al, 2000, 2003Meehan et al, 2001) and convicted (Huss & Langhinrichsen-Rohling, 2006) samples. However, when other alternative batterer typologies were established, psychopathy proved to be useful to identify a specific batterer subtype characterized by displaying pathologically high anger levels (Eckhardt et al, 2008;Murphy et al, 2007), perpetrating premeditated (Stanford et al, 2008) and proactive IPV (Chase et al, 2001) and repeatedly reassaulting their partners (Gondolf & White, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathy failed to differentiate among batterer subtypes according the traditional batterer typologies. First, both Babcock et al (2004) and Meehan et al (2001) reported that psychopathy was not a useful variable to differentiate between the type 1 and type 2 batterers proposed by Paper Sample Assessment Relevant findings Babcock et al (2004) Couples (N = 102) from community sample a • Target groups: clinical (n = 50) and low (n = 22) level violent men • Control group: non intimate partnerviolent men (n = 30) Target and control groups were created based on both self-and female partnerreports on male-to-female IPV (CTS2): clinical level (at least six minor, two moderate or one severe male-to-female IPV act in the past year), low level (at least one minor o moderate male-to-female IPV act in the past year), and control group (no male-to-female IPV in the past 5 years and no serious violence ever) 100% male (couples) Mean men's age (SD): 32 (9.6) P: SRP-II IPV: CTS2 (self-and female partnerreports)…”
Section: •The Role Of Psychopathy In Batterer Typologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the family only group, these typologies seem to converge in identifying a group of men who are high in general antisocial behavior and a group who may still be elevated in antisocial behavior to some degree, but also show depressive/anxious and borderline personalities. However, at least two studies have failed to replicate the Gottman et al typology (Babcock, Green, Webb, & Graham, 2004;Meehan, Holtzworth-Munroe, & Herron, 2001), and there have been no consistent replications.…”
Section: Principal Batterer and Violence Typologiesmentioning
confidence: 99%